Good Corporate Governance Memoderasi Pengaruh Audit Manajemen terhadap Kinerja Manajerial (Studi Empiris pada Perusahaan Perbankan di Pekanbaru) - Savitri, Enni (Jurnal Aplikasi Manajemen, 2016)
This study aimed to analyze the ability of Good Corporate Governance Moderating TheEffect of Audit Management to managerial performance, analyze Good Corporate Governance moderating the effectof internal control to managerial performance. The population of this studyis all of managerial from 20 banking companiesin Pekanbaru amounted 60 people. The respondents are the Chairman of the Audit Committee, Head of the company's internal control system and Head of Operations. In this study, sampling was done by the distribution of questionnaires that distributed to the entire managerial banks in Pekanbaru. The type of data in this study is primary data. Analysis tool used Moderate Regression Analysis (MRA). The results showed that Good Corporate Governance able to moderate the effectof management audit to managerial performance of banking in Pekanbaru. Good corporate governance able to moderate the effect of the internal control to managerial performance of banks in Pekanbaru.